Public Knowledge of Heart Attack in a Population Survey in Nepal - Limbu, Yuva Raj; Malla, Rabi; Regmi, Shyam Raj; Dahal, Ramesh; Yonjan, Ganesh; Gartaula, Ritu Prasad (Nepalese Heart Journal, 2004)
Limited knowledge of heart attack symptoms causes patients’ delay for early time Dependant thrombolytic therapy, which offers impressive survival benefit. Previous studies carried out in developed countries demonstrated the deficient of knowledge about wide range of heart attack symptoms. This study first reveals public awareness and knowledge of heart attack symptoms in developing country Like Nepal,